Comparison of Problem Based Learning and Guided Discovery Learning in Terms of Students’ Mathematical Problem-Solving Ability - Stiadi, Elwan; Fitriani, Fitriani; Yanwar, Amanda Pradhani; U-Sin, Nader (Universitas Islam Ahmad Dahlan (UIAD), 2024)
This study is quasi-experimental research. This study was conducted in the eight grade at SMPN 4 Bengkulu City for the 2021–2022 academic year. Two experimental groups were selected randomly from eight classes. After performing normality and homogeneity tests, a sample of class A was made up of 31 students who received Problem Based Learning (PBL) model treatment and class C was made up of 30 students who received Guided Discovery Learning (GDL) model treatment. In this study, two types of data analyses—descriptive data analysis and inferential analysis—were used. The data on the students’ problem-solving ability before and after treatment were described using descriptive analysis. The t-test of two independent sample means, which compares the means of two separate samples, was used to compare differences in the efficacy of learning models with PBL and GDL on students' ability to solve mathematical problems. The result shows that the ability to solve mathematical problems on average using the PBL model and the GDL approach is equivalent.